The Fearful Paradise of “The Life of Basil the Younger” - Svetlana A. Borisova (Studia Litterarum)
Emotive vocabulary played a significant role in creating the image of paradise in the literary works that circulated in Ancient Russia. The article explores the meaning of the adjective “fearful” and its cognates. “The Life of Basil the Younger” was chosen as a historical source, in which references to fear are most common. Based on the comparison of the original text of “The Life…” and its Slavonic translation, the article identifies the Greek equivalent of the Old Russian “fear in paradise”, which is a special kind of emotion — φρίκη. Examples from other sources confirm the established connection. Analysis of Ancient Greek texts made it possible to trace the origins of the concept φρίκη, the changes in its meaning over time, and the main aspects of this state. The author also examines connection between fear-φρίκη and the words that designate the emotion of wonder.. As a result of our research, we got the complex understanding of the concept of fear not only in the descriptions of paradise, but also in the stories where characters are faced with the Divine.